HUBUNGAN FAKTOR PSIKOSOSIAL DENGAN DISABILITAS PADA PERAWAT RUMAH SAKIT HASAN SADIKIN DENGAN NYERI PUNGGUNG BAWAH - Dwi Hany Febrina S, Henny Anggraini, Yustiani Dikot (NEURONA, 2009)
INTRODUCTION PAIN AND DISABILITY IN PATIENT WITH LOW BACK PAIN LBP ARE INFLUENCED BY PHYSICAL AND PHYSICOSOCIAL FACTORS THESE PSYCHOSOCIAL FACTORS ARE USUALLY REFERRED TO AS YELLOW FLAGS WHICH CONSIST OF JOB DISSATISFACTION MOOD ANNOYANCE WHICH CAN CATEGORIZED AS FEAR AVOIDENCE BELIEF FAB ANXIETY AND DEPRESSION EVALUATING THESE FACTORS IS USEFUL TO IDENTIFY WHICH PATIENT WILL HAVE LONGTERM DISABILITY AND ALSO USEFUL FOR THE CLINICIANS IN CHOOSING TREATMENT TO INCREASE PROGNOSIS OR REDUCE DISABILITY THE AIM OF THIS STUDY WAS TO IDENTIFY THE CORRELATION BETWEEN PSYCHOSOCIAL FACTORS AND DISABILITY IN NURSES WITH LBP IN DR HASAN SADIKIN HOSPITAL BANDUNG